Improving Ecotourism Inclusion for People with Disabilities : Community-Based Strategies in Ternate, Indonesia - Patilaiya, Hairudin La; Probandari, Ari Natalia; ., Hartono; ., Sunarto (Journal of Ecohumanism, 2025)
This study examines the effectiveness of a community-based intervention in enhancing public knowledge, attitudes, and behavior toward ecotourism accessibility for people with disabilities in Ternate, Indonesia. Grounded in participatory intervention and behavioral change theories, this research addresses public awareness gaps through educational programs and informational materials, aiming to foster more inclusive tourism experiences. Using a quasi-experimental design with a control group, the study involved 287 participants selected via Cluster Random Sampling from a population of 4,964 residents. The intervention was conducted at three major ecotourism destinations in Ternate: Sulamadaha Beach, Tolire Besar Lake, and Batu Angus Geotourism. Findings indicate a statistically significant improvement in community knowledge (N-Gain = 0.31, p < 0.05) and moderate gains in attitudes and behavior (N-Gain = 0.07, p < 0.05), with notable differences between experimental and control groups. These results underscore the role of participatory approaches in shaping inclusive tourism policies and practices, particularly in ecotourism settings. However, the limited impact on attitudes and behavior suggests the need for extended interventions, reinforcement strategies, and multi-stakeholder collaboration, including policymakers and tourism industry stakeholders. This study contributes to discussions on participatory interventions in tourism development and provides empirical insights for designing policies that integrate accessibility into sustainable ecotourism planning.